Defect Engineering in Metal‒Organic Frameworks as Futuristic Options for Purification of Pollutants in an Aqueous Environment - Cao, Yuhua; Mi, Xin; Li, Xiang; Wang, Bo (Frontiers in Chemistry, 2021)
Clean water scarcity is becoming an increasingly important worldwide issue. The water treatment industry is demanding the development of novel effective materials. Defect engineering in nanoparticles is among the most revolutionary of technologies. Because of their high surface area, structural diversity, and tailorable ability, Metal‒Organic Frameworks (MOFs) can be used for a variety of purposes including separation, storage, sensing, drug delivery, and many other issues. The application in wastewater treatment associated with water stable MOF‒based materials has been an emerging research topic in recent decades. Defect engineering is a sophisticated technique used to manufacture defects and to change the geometric framework of target compounds. Since MOFs have a series of designable structures and active sites, tailoring properties in MOFs by defect engineering is a novel concept. Defect engineering can excavate hidden active sites in MOFs, which can lead to better performance in many fields. Therefore, this technology will open new opportunities in water purification processes. However, there has been little effort to comprehensively discuss this topic. In this review, we provide an overview of the development of defect engineered MOFs for water purification processes. Furthermore, we discuss the potential applications of defect engineered materials.